Rhetorical Strategies in Teaching Skills: A Systematic Review from 2019 to 2024 - Dachi, Marta Izona Ellen; Azriansyah, M Renaldi (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
The article presents a systematic review of research on rhetorical strategies in teaching skills, aiming to provide a comprehensive understanding of the current state of the research in this area from 2019 to 2024, and to gain a comprehensive understanding of the role of rhetorical strategies and explore future research trends. The researcher used the theory of Templier and Pare in conducting a review article. After collecting the article based on some databases, the researcher found 672 articles. Moreover, after data selection and screening followed the protocol criteria, 14 articles were included in this study. The results show that there are some rhetorical strategies in teaching listening skills applied. Those are traditional and modern methods, and mostly used bottom-up strategy by Richard’s theory. The findings of this review provide valuable insights for educators, curriculum developers, and researchers interested in improving listening skills.